PENCIPTAAN FILM DOKUMENTER “MAHANTAK KUDO” RASIONALISASI PERUBAHAN TERHADAP AKTIFITAS ADAT - Ediantes Ediantes (Jurusan Seni Rupa, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2019)
The development of Kudo dance is a phenomenon that occurs in the Kerinci region, the Kudo dance dance is not only presented as a tradition value that is not recognized, but is a traditional dance that is recognized by ninik mamak holders of the legitimacy of Kerinci culture, by contributing to the people This custom then the presence of the Rantak Kudo dance is recognized as a traditional dance from them. Although in plain view this dance is not a dance that fully uses traditional tools. This objective reality is used as a presentation in this film entitled Mahantak Kudo. It is expected that the concepts that will be carried out such as the exploration of dancers and the role of the mamak ninik and traditional management of the preservation of dance are able to enrich the meaning and culture, especially in Indonesia. The film is expected to be able to rationalize a cultural phenomenon that is interpreted creatively. This objective reality is used as the main material in the production of documentary films in the style of Cinema Verite. The work will be interpreted by applying the aesthetic concept of the director, so that a new perspective for connoisseurs will be created which results from the aesthetic concept of the workman without changing the substantive aspects of the Kudo dance dance itself.